Quality Characterization of Celery ( Apium graveolens L.) by Plant Zones and Two Harvest Dates - Guerra, Natalia (2010)
The aim of this study was to characterize the quality of celery petioles (Apium graveolens L. cv Golden Clause) from the external, middle, and internal zones of each plant. Harvest dates were 93 (HD1) and 124 (HD2) days after transplantation. Total weight (TW), total length (TL), total leaves number (LN), and petiole length of leaves (PL) for the 3 zones were measured. Physicochemical (color, b∗ and h; texture; total soluble solids, TSS; titratable acidity, TA; water content, WC), nutraceutical (ascorbic acid, AA; total quinones, TQ; browning potential, BP), and sensorial analysis (flavor, fibrosity, crunchiness) were done at harvest on petioles of each zone. No differences between harvesting dates were found in TW, TL, LN, and PL. Middle leaves had the highest PL. Harvest dates were not different in b∗, h, TA, AA, and WC. Texture, TSS, BP, and TQ resulted higher in petioles of HD2 than in HD1. Similar TSS and TA were found in leaves of different plant zones. The yellow color of both external and internal zones was significantly higher than in the middle zone. The texture and BP was similar between the external and middle zones but the WC was lower in the external zone. Similarly, the AA content as well as the TQ was also lower than in the middle zone. Harvest delay improved the nutraceutical value in terms of BP and TQ, even though it also resulted in pithiness and fibrosity of the leaves. This study therefore suggests that the petioles of the middle zone when harvested at HD1 are the most suitablefor consumption.